Pengaruh Pemanfaatan Teknologi Digital dan Inovasi terhadap Kesiapan Berwirausaha Mahasiswa - Khairunnisa Al Mas; Sabrina Erisa Aulia Sihotang; Rani Rani; Sekina Teodora br Pelawi; Susi Pasaribu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Students’ entrepreneurial readiness has become an important concern in responding to the limited availability of formal employment opportunities in Indonesia. Digital technology and innovation are considered key factors that may foster the emergence of independent young entrepreneurs. This study aims to analyze the effect of digital technology utilization and innovation on students’ entrepreneurial readiness. A quantitative approach with explanatory research was employed, involving 70 students of the Faculty of Economics, Universitas Negeri Medan. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The research instrument was proven valid and reliable, and the regression model met all classical assumption tests. The findings reveal that digital technology has a significant positive influence on entrepreneurial readiness, while innovation shows a significant negative effect, indicating challenges in its practical application among students. Simultaneously, both variables significantly affect entrepreneurial readiness, with a contribution of 33.13%. These results highlight the dominant role of digital technology in enhancing entrepreneurial readiness, whereas innovation tends to be perceived as a burden due to the need for greater capital, skills, and risk-taking. In conclusion, higher education institutions should strengthen students’ digital literacy while providing adequate support to ensure innovation can be effectively managed to foster entrepreneurial readiness.